An investigation of the ergonomics and biomechanics of rifle shooting from the standing position - Smith, Jan Ryno (Division of Biomedical Engineering, 2017)
The purpose of this study was to investigate the ergonomics and biomechanics of rifle shooting from the standing position. At present, the scientific literature on shooting contains primarily qualitative descriptions of the various aspects of the sport. Quantitative data on the kinetic and kinematic aspects of standing rifle shooting was collected in the present thesis. Transducers were developed to measure foot forces in the vertical and horizontal plane, recoil force on the shoulder and the grip force of the trigger hand. Kinematic data was collected with a video camera. The study revealed that recoil energy was dependent on the attributes of the shooter. Handgrip forces were found to be well below the maximum handgrip strength. An exploratory investigation of the interrelationships among foot forces, rifle recoil and angular and linear displacements was carried out. No horizontal foot forces to counteract the recoil force were observed. A possible explanation for the finding is proposed. The findings are discussed with reference to the ergonomic implications for rifle stock design. Further investigations of the relationships between shooting performance and the man-rifle interface are indicated.